Health education to promote self-care during hospitalization of patients with Type 2 Diabetes - Peña, Amalia Priscila; Venegas, Blanca Cecilia; Obando, Jorge Alejandro (Universidad y Salud, 2020)
Introduction: Type 2 Diabetes is a global public health problem that currently shows a high recurrence of hospitalizations due to a lack of self-care, which could be improved through health education. Objective: To assess the capacity of self-care agency in hospitalized patients with type 2 Diabetes before and after a health education intervention. Materials and methods: A prospective, quasi-experimental, pre-test/post-test study with a single population group of 76 patients. The Self-Care Agency Scale (SAS) was applied, using a CronBach alpha of 0.74 to measure self-care. A video was designed as the health education intervention to promote self-care. Results: Before the intervention, 87.3% of the study population showed a low capacity for self-care agency. However, this percentage decreased to 45.9% after the intervention. Conclusions: Health education during hospitalization of patients with Type 2 Diabetes triggers changes in their self-care capacity as it encourages healthy lifestyles and motivates health professionals to provide patient care with an increased focus on health education.